Institutional improvements in readability of written informed consent forms sustained post-revised Common Rule. Issue 1 (30th September 2021) - Caballero, Alison; Leath, Katherine J.; Gan, Jennifer M.
Abstract: Obtaining informed consent is a fundamental and ethical practice within human subjects' research. Informed consent forms (ICFs) include a large amount of information, much of which may be unfamiliar to research subjects, and the revised Common Rule resulted in several required additions to that language. As limited health literacy impacts many potential subjects, efforts should be made to optimize subjects' ability to read and understand ICFs. In this brief report, we describe an assessment of ICFs at an academic medical center to evaluate longitudinal changes in readability with the introduction and update of a plain language ICF template.